Comparison of Ushul Al-Hukm With Western Legal Theory - Latif, Muhammad Sabri; Hanafi, Yusuf; Hadi, Rizal; Zulhelmi, Zulhelmi; Ilyas, Ahmad Ghufran (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2023)
This article is the result of a review of the book